2016
DOI: 10.1038/nmicrobiol.2015.21
|View full text |Cite
|
Sign up to set email alerts
|

The microenvironment of injured murine gut elicits a local pro-restitutive microbiota

Abstract: The mammalian intestine houses a complex microbial community, which influences normal epithelial growth and development, and is integral to the repair of damaged intestinal mucosa1–3. Restitution of injured mucosa involves the recruitment of immune cells, epithelial migration and proliferation4,5. Although microenvironmental alterations have been described in wound healing6, a role for extrinsic influences, such as members of the microbiota, has not been reported. Here, we show that a distinct subpopulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
163
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(170 citation statements)
references
References 31 publications
(70 reference statements)
6
163
0
1
Order By: Relevance
“…No similar gastrointestinal reaction was observed after they resumed normal diets for 7 d. We therefore inferred that fermentation of prebiotics formula facilitated the production of gas in intestinal tract. The 16S rRNA sequencing results showed the increase in probiotics such as Bifidobacterium and Akkermansia after one-week FF [40][41][42][43][44]. The most worthy of attentions were the increase in overall abundance and complexity of microorganisms, and the same increase after resuming normal diet for 7 d, which is represented by species richness and Shannon-Wiener Index.…”
Section: Discussionmentioning
confidence: 99%
“…No similar gastrointestinal reaction was observed after they resumed normal diets for 7 d. We therefore inferred that fermentation of prebiotics formula facilitated the production of gas in intestinal tract. The 16S rRNA sequencing results showed the increase in probiotics such as Bifidobacterium and Akkermansia after one-week FF [40][41][42][43][44]. The most worthy of attentions were the increase in overall abundance and complexity of microorganisms, and the same increase after resuming normal diet for 7 d, which is represented by species richness and Shannon-Wiener Index.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings of Alam et al ,36 this graph shows the different changes that occur in the microbiota according to the intestinal injury. It shows the important role of the wound-mucosa-associated microbiota in initiating the early healing cascade by stimulating pro-restitutive signalling and increasing cell migration and proliferation.…”
Section: The Impact Of Preoperative Mechanical Bowel Preparation Withmentioning
confidence: 99%
“…Another recent study by Alam et al 36 elegantly shows that both mechanisms of action may coexist to induce intestinal repair upon injury (box 1). They found that Akkermansia muciniphila administration plays a major role in wound healing by creating a specific environment and local environmental changes.…”
Section: Molecular Mechanisms Linking Microbiota Signalling and Woundmentioning
confidence: 99%
“…In addition, investigations utilizing germ-free mice have established a function for the gut microbiome and metabolic regulation [8]. The gut microbiome has also been shown to positively influence homeostasis of the intestinal mucosa by enhancing barrier function, as well as epithelial cell proliferation and survival [9][10][11][12][13][14][15]. For instance, villi of the small intestine of the germ-free mice have impaired angiogenesis [16] and have slower turnover rates of epithelial cells [17].…”
Section: The Intestinal Physiology and Eukaryotic-prokaryotic Interacmentioning
confidence: 99%